Informal caregivers and care burden in Iran: Systematic review and meta-analysis - Mohammadreza Amiresmaili; Reza Goudarzi; Leila Agoush (Wolters Kluwer Medknow Publications, 2023)
Background: The increase in the average age of the population, the decrease in the size of the household and rising in the number of working women impose an increasing burden on home caregivers in Iran. The aim of this study was to measure care burden of informal caregivers in Iran through systematic review and meta-analysis of existing literature. Materials and Methods: A systematic review was conducted by using national and international databases of Scopus, PubMed, Embase, Web of Science, SID, Magiran, and IranDoc papers in English and Persian language up to the first half of 2020. In this meta-analysis, we calculated the pooled care burden and 95% confidence intervals in Statistical Software For Data Science (STATA) V.15. Results: Forty-four papers were included in the current study based on inclusion and exclusion criteria comprising of 8626 samples. Pooled mean of Burden of Care was 52.01 (95% CI: 48.21-55.82). Highest pooled mean(SD) of care burden (64.37) was related to caregivers of schizophrenia patients (95% CI: 56.09-72.64). Highest care burden (53.45) was observed in most deprived areas (95%CI = 47.05-59.86). A statistically significant relationship was observed between caregivers gender and care burden (p < 0.05). Conclusions: The reported care burden of informal caregivers requires the establishment of a support system to control mental and physical stress. Due to the dispersion and cultural diversity in Iran, more studies are needed to obtain more accurate data.